1982
DOI: 10.1083/jcb.94.1.150
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational modification of a neurofilament protein during axoplasmic transport: implications for regional specialization of CNS axons

Abstract: The possibility that proteins are modified during axoplasmic transport in central nervous system axons was examined by analyzing neurofilament proteins (200,000, 140,000, and 70,000 mol wt) along the mouse primary optic pathway (optic nerve and optic tract). The major neurofilament proteins (NFPs) exhibited considerable microheterogeneity. At least three forms of the " 140,000" neurofilament protein differing in molecular weight by SDS PAGE (140,000-145,000 mol wt) were identified. The "140,000" proteins, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 53 publications
4
68
0
Order By: Relevance
“…Although posttranslational cleavage of protein Gainer and Same, 1977;Nixon et al, 1982) and glycosylation (Ambron and Treistman, 1977) occur during the axonal transport of other proteins, our studies provided no evidence for interconversion or modification of the 2 major NCAM polypeptides detected along the optic nerve, chiasm, or tract. Furthermore, the ratio of radioactivity in the 2 higher-molecular-weight NCAM forms in the tectum did not differ between samples harvested 2 or 16 hr after injection.…”
Section: Amount Of Ncam In the Fcmentioning
confidence: 62%
“…Although posttranslational cleavage of protein Gainer and Same, 1977;Nixon et al, 1982) and glycosylation (Ambron and Treistman, 1977) occur during the axonal transport of other proteins, our studies provided no evidence for interconversion or modification of the 2 major NCAM polypeptides detected along the optic nerve, chiasm, or tract. Furthermore, the ratio of radioactivity in the 2 higher-molecular-weight NCAM forms in the tectum did not differ between samples harvested 2 or 16 hr after injection.…”
Section: Amount Of Ncam In the Fcmentioning
confidence: 62%
“…Other proteins are thought to be modified during axonal transport: there is proteolysis of neurophysin, accompanying peptide processing (20); axonal glycosylation of proteins in a giant neuron of Aplysia (21); and proteolysis or regional sorting of cytoskeletal components of slowly transported proteins (22,23). Here the proportion of a, however, neither increased nor decreased significantly with time after its appearance in the optic nerve and the target areas.…”
Section: Discussionmentioning
confidence: 90%
“…It should be mentioned that FNP7 identifies selected sites on the upper and lower forms of the various NF-M bands and indicates that the apparent molecular weight of NF-M on SDS-PAGE may shift due to the content of phosphate, with a faster migration in the gels after dephosphorylation. Nixon and colleagues (Nixon et al, 1982(Nixon et al, , 1994aNixon and Logvinenko 1986) reported the presence of several NF-M species that differed along the transport in the mouse primary optic pathway. The presence of one NF-M gene (Napolitano et al, 1987) but the presence of several NF-M forms suggests that this variety is generated by posttranslational modifications such as phosphorylation or by the addition of O-linked N-acetylglucosamines (Dong et al, 1993).…”
Section: Phosphorylation Of Nf-m Adds To Cell Specificitymentioning
confidence: 97%